'I am who I am': Reputation concerns in adolescents on the autism spectrum. (May 2016) - Cage, Eilidh; Bird, Geoffrey; Pellicano, Liz
Highlights: Some autistic adolescents can be concerned about reputation. Autistic adolescents desired a reputation for being different and wanted acceptance. Findings have implications for inclusion practices in schools. Abstract: Background: Adolescence is often characterised by an increased concern for one's reputation in typical development. The extent to which autistic adolescents are concerned for their reputation, however, is unclear. Method: Semi-structured interviews were conducted with 12 autistic adolescents and five members of school staff to examine reputation concerns in autism. Topics discussed included being 'cool', friendships, worries and self-concepts. Results: Thematic analysis revealed that autistic adolescents were sometimes concerned about their reputation, although many reported that they did not want to be cool. Instead, they preferred to be true to themselves and struggled to understand the rules of being cool. Adolescents' difficulties in coping with unpredictability also contributed to their understanding of social rules. Findings were supported by the responses of school staff. Conclusions: This study suggests that autistic adolescents can be concerned about their reputation, with some wishing to be accepted for having a reputation for being different.